Bistable chiral nematic liquid crystal device switchable between the transmissive and reflective modes. Issue 1 (2nd January 2016) - Kim, Ahn-Ki; Yoon, Tae-Hoon
Abstract : Proposed herein is a single-panel liquid crystal device that is switchable between the transmissive and reflective modes without subpixel division. Dye-doped liquid crystals were used to eliminate the image inversion caused by a reflective polarizer. The splay and π -twist states of the bistable chiral splay nematic mode, which has two stable states, were employed for a good dark state in both the transmissive and reflective modes. Operation in the transmissive mode can be achieved by applying an in-plane field, whereas a vertical field is applied for operation in the reflective mode. It is expected that the proposed device can be used as a highly efficient transflective device for outdoor as well as indoor environments.